Effect of behavioural change communication through women development army on optimal complementary feeding practice among children aged 6–23 months in Southwest Ethiopia: a cluster randomized controlled trial - Meseret Tamrat Gebretsadik; Dessalegn Tamiru; Assefa Legesse Sisay; Tefera Belachew (Nutrition Journal)
Abstract Background Optimal development and growth in children are primarily determined by dietary practice during the first 24 months of life. However, in low-income countries, especially in sub-Saharan Africa, ensuring adequate nutrition and maternal nutritional knowledge are challenging. As a result, it is a major public health issue in Ethiopia. Therefore, it is essential to address feeding practices and knowledge gaps through behavior change communication. This study assessed the effect of behaviour change communication through the women’s development army on complementary feeding practices among children aged 6–23 months in Jimma Zone, Ethiopia. Methods A cluster randomized controlled trial was conducted from December 2021 to November 2022 in rural Ethiopia. The study used two-stage cluster sampling to allocate villages into control and intervention groups and systematic random sampling methods to select participants. Fourteen villages were randomly chosen from 21 eligible ones, with seven clusters (villages) in each group. Initially, 438 mother-child pairs participated, and 404 pairs remained at the endline data collection. The intervention group, consisting of 219 pairs, received food-based BCC from the WDA, while the control group, also with 219 mother-child pairs, received routine health education by Health Extension workers. Data were collected through structured questionnaires and 24-hour dietary recall. The primary objective for this study was optimal complementary feeding practices. The chi-square statistic assessed sociodemographic differences, and the difference-in-differences method evaluated the intervention’s effect. Generalized estimating equations were used to analyze BCC’s impact and identify predictors. Results The intervention group showed a 28.4% (DID: 28.4%, 95% CI: 18.1 to 38.6) improvement in optimal complementary feeding practices compared to the control group (p < 0.001). Factors associated with optimal complementary feeding practices included BCC (AOR = 5.00, 95% CI: 1.78–14.05), maternal education (AOR = 2.00, 95% CI: 1.33–3.01), not using traditional food processing methods (AOR = 0.34, 95% CI: 0.21–0.54), and maternal knowledge (AOR = 0.65, 95% CI: 0.43–0.99). Conclusion BCC, through the WDA, significantly improved complementary feeding knowledge and practices. Policymakers should support long-term BCC interventions and adopt a multi-sectoral approach to address the factors influencing child feeding practices. The study is registered retrospectively in the Pan African Clinical Trials Registry with number PACTR202106621156513 on 21/06/2021.